Statin therapy upregulates arachidonic acid status via enhanced endogenous synthesis in patients with plaque psoriasis. (May 2022) - Garshick, Michael S.; Block, Robert; Drenkova, Kamelia; Tawil, Michael; James, Genevieve; Brenna, J. Thomas
Highlights: In patients with psoriasis, atorvastatin reduces linoleic acid and increases arachidonic acid in vivo. Atorvastatin upregulates circulating transcripts fatty acid desaturase 1 and 2 in vivo. Our results suggest a possible interaction between statins and fatty acid synthesis in psoriasis. Abstract: Circulating fatty acids (FA) may be important in the psoriatic pro-inflammatory phenotype. FADS1 converts linoleic acid (LA) to arachidonic acid (AA), a precursor to potent signaling molecules. HMG-CoA reductase inhibitors (statins) increase FADS1/2 expression in vitro. Psoriasis patients (42 ± 14 years/age, 47% male) were randomized to 40 mg of atorvastatin ( n  = 20) or nothing ( n  = 10) for two weeks and plasma FA measured pre and post treatment. After treatment, LDL-C was 44% lower in the statin compared to the no-treatment group. Statins increased FADS1/2 expression, and lowered LA 12% (33% – > 29%, p <0.001) and raised AA 14% (7.7% – > 9.0%, p <0.01) with no change in the no-treatment group. In psoriasis, statins enhance AA and decrease LA, consistent with the action of enhanced FADS expression in vivo. Therapies intended to blunt the effects of AA on platelet aggregation, such as aspirin or omega-3 fatty acids, may require dose adjustment when co-administered with atorvastatin. NCT: NCT03228017